Development of Deep Brain Stimulation for the Treatment of Resistant Depression - Canavan, Neil (MD Conference Express, 2008)
Although a variety of treatments for major depression are available, less than 40% of patients achieve remission with their first treatment [Rush AJ et al. Am J Psychiatry 2006], and approximately 10% becomes treatment-resistant over time. New treatments are needed for patients who remain depressed despite having tried all available therapies. This article discusses the use of deep brain stimulation as a treatment for patients with chronic, treatment-resistant depression who have failed all other therapies.